Relationships among Store Image and Store Loyalty in Slovenia - Miran Grah; Polona Tominc (Naše gospodarstvo/Our economy, 2015)
Image has become one of the most important factors of stores’ survival and development. In this paper, a model of relationships among the multidimensional variables of store image, positive affect, satisfaction with the store, trust and commitment to the store is formed and tested with a sample of 209 customers in three stores in the Pomurje region of Slovenia. The important conclusion of the research is that several interrelations among store image, positive affect, satisfaction, trust and store commitment exist. The results also show significant gender differences in perceptions of store image. These results provide several important insights for managing supermarkets in the Slovenian market and are also important for future research.